Utilization of Mental Health Services After Mild Pediatric Traumatic Brain Injury - Jimenez, Nathalia (Pediatrics, 2017)
BACKGROUND: Mild traumatic brain injury injuries (mTBIs), including concussions, represent >2 million US pediatric emergency department visits annually. Post-mTBI mental health symptoms are prominent and often attributed to the mTBI. This study examined whether individuals seeking post-mTBI mental health care had previous mental health diagnoses or a new onset of such disorders, and determined if mental health care utilization differed by race/ethnicity. METHODS: Retrospective cohort study, using the Medicaid Marketscan claims national dataset (2007–2012). Utilization of mental health services 1 year before and 1 year after mTBI was compared between children with and without mental health diagnoses before injury. Primary outcome was receipt of post-mTBI outpatient mental health care. RESULTS: A total of 31 272 children 20 years or younger were included, 8577 (27%) with mental health diagnoses before their mTBI and 22 695 without one. After injury, children without previous mental health disorders increased mental health services utilization; however, most (86%) postinjury mental health care was received by children with previous mental health disorders. Having a mental health diagnosis pre-mTBI was the most important risk factor for receiving post-mTBI mental health care (odds ratio 7.93, 95% confidence interval 7.40–8.50). Hispanic children were less likely to receive post-mTBI mental health care. CONCLUSIONS: mTBI was associated with increased utilization of mental health services but most of these services were received by children with previous mental health disorders. Our documentation of racial/ethnic disparities in mental health care utilization reemphasize the importance of providing individualized, culturally, and linguistically competent care to improve outcomes after mTBI for all children.